Treatment of hyperuricemia, gout and other crystalline arthritidies - F. Lioté (PAGEPress Publications, 2012)
Gout is a very common joint disease which is due to chronic hyperuricemia and its related articular involvements. Yet it can be cured when appropriately managed. Comprehensive management of gout involves correct identification and addressing all causes of hyperuricemia, treating and preventing attacks of gouty inflammation (using colchicine NSAIDs, and/or steroids), and lowering serum urate (SUA) to an appropriate target level indefinitely. The ideal SUA target is, at a minimum, less than 6 mg/dL (60 mg/L or 360 μmol/L), or even less than 5 mg/dL in patients with tophi. The SUA target should remain at less than 6 mg/dL for long in all gout patients, especially until tophi have resolved. Patient education and adherence to therapy are key point to the optimal management of gout, aspects which are often neglected. Adherence can be monitored in part by continuing, regular assessment of the SUA level. More difficult cases of gout often need a combination of urate lowering therapy (ULT) for both refractory hyperuricemia and chronic tophaceous arthritis. Chronic tophaceous gouty arthropathy which do not respond adequately to optimized oral ULT might benefit from the use of pegloticase, when this is available in, for example, Italy and other European countries. By contrast, in calcium pyrophosphate (CPP) crystal deposition disease (CPPD), as evidenced by pseudo gout attacks or chronic polyarthritis, similar anti-inflammatory strategies have been recommended, but there have as yet been no controlled trials. Of note, there is no treatment for the underlying metabolic disorders able to control the CPPD. Management of crystal-induced arthropathies (CIA) depends not only on clinical expression, namely acute attacks or chronic arthropathy, but also on the underlying metabolic disorder. We will mainly focus on gout as an archetype of CIA.